Biopigment produced by Monascus purpureus MTCC 369 in submerged and solid state fermentation: a comparative study. Issue 6 (6th November 2017) - Sehrawat, Rachna; Panesar, Parmjit S.; Panesar, Reeba; Kumar, Anit
Abstract : Purpose: Biopigments, natural colors from microbiological origin are of great interest because of their potential advantages over synthetic colorants. Therefore, this paper aims to evaluate the best possible fermentative conditions for the maximum production of biopigment using solid state fermentation and submerged fermentation by Monascus purpureus MTCC 369. Design/methodology/approach: The biopigment was produced using solid state fermentation and submerged with optimized substrate to achieve higher yield. The statistical analysis was carried out using a Microsoft Excel ® (Microsoft Corporation). Findings: On comparative analysis, it was observed that solid state fermentation resulted significant accumulation of biopigment (9.0 CVU/g) on the 9th day in comparison to submerged fermentation (5.1 CVU/g) on the 15th day. Practical implications: Results revealed that sweet potato peel powder and pea pods provides necessary nutrients required for mycelial growth, and biopigment production, therefore, can be used as potent substrate for biopigment production by Monascus purpureus MTCC 369. Extracted color can be used in confectionery, beverages and pharmaceutical industries. Originality/value: This work focuses on utilisation of waste for production of pigment as alternative source to synthetic colorant, and few studies have been carried out using wastes, but no work has been carried out on sweet potato peel to the best of the authors' knowledge.